IGFBP-rP1 suppresses epithelial–mesenchymal transition and metastasis in colorectal cancer - Zhu, S (Cell Death Dis, 2015)
Epithelial–mesenchymal transition (EMT) was initially recognized during organogenesis and has recently been reported to be involved in promoting cancer invasion and metastasis. Cooperation of transforming growth factor-β (TGF-β) and other signaling pathways, such as Ras and Wnt, is essential to inducing EMT, but the molecular mechanisms remain to be fully determined. Here, we reported that insulin-like growth factor binding protein-related protein 1 (IGFBP-rP1), a potential tumor suppressor, controls EMT in colorectal cancer progression. We revealed the inhibitory role of IGFBP-rP1 through analyses of clinical colorectal cancer samples and various EMT and metastasis models in vitro and in vivo. Moreover, we demonstrated that IGFBP-rP1 suppresses EMT and tumor metastasis by repressing TGF-β-mediated EMT through the Smad signaling cascade. These data establish that IGFBP-rP1 functions as a suppressor of EMT and metastasis in colorectal cancer.